2003
DOI: 10.1590/s0103-50532003000300023
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted extraction of Ca, K and Mg from in vitro citrus culture

Abstract: Apresenta-se um procedimento para extração de Ca, K e Mg de amostras de cultivo in vitro de plantas, comparando-se culturas de calo com diferentes potenciais embriogênicos de Citrus sinensis e Citrus limonia, com o emprego de energia ultra-som. Foram investigados os parâmetros relacionados com a extração de metais, tais como tipo de amostragem do material, concentração do ácido e tempo de sonicação. Visando a comprovação da exatidão, o procedimento de extração ultra-sônica foi comparado com o de digestão ácida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 20 publications
1
11
0
3
Order By: Relevance
“…Wang and Weller (2006) cited that scanning electron micrographs (SEM) have provided evidence of the mechanical effects of ultrasound, mainly shown by the destruction of cell walls and release of cell contents. Our results also agree with some other authors (Minami, 1996;Simal et al, 1998;Nascentes et al,2001;Yebra and Moreno, 2002;Arruda et al, 2003;Banjoo and Nelson, 2005;Gu et al, 2005;and Herrera and Luque de Castro, 2005), who have stated that ultrasound increases the extraction levels not only of polyphenols but ions (Cu, Fe, K, Mg Mn, Pb, Se, Zn) and other compounds such as polycyclic aromatic hydrocarbons and water that are present in different biological materials such as citric cultures, seafood, tobacco, strawberries, lettuce, cabbage and apples. …”
Section: Effect Of Ultrasound Exposure Time On the Total Extractive Ysupporting
confidence: 93%
See 1 more Smart Citation
“…Wang and Weller (2006) cited that scanning electron micrographs (SEM) have provided evidence of the mechanical effects of ultrasound, mainly shown by the destruction of cell walls and release of cell contents. Our results also agree with some other authors (Minami, 1996;Simal et al, 1998;Nascentes et al,2001;Yebra and Moreno, 2002;Arruda et al, 2003;Banjoo and Nelson, 2005;Gu et al, 2005;and Herrera and Luque de Castro, 2005), who have stated that ultrasound increases the extraction levels not only of polyphenols but ions (Cu, Fe, K, Mg Mn, Pb, Se, Zn) and other compounds such as polycyclic aromatic hydrocarbons and water that are present in different biological materials such as citric cultures, seafood, tobacco, strawberries, lettuce, cabbage and apples. …”
Section: Effect Of Ultrasound Exposure Time On the Total Extractive Ysupporting
confidence: 93%
“…Studies of ultrasound application during osmotic dehydration of apples have demonstrated that there is an increase of mass transfer after applying ultrasound waves on samples (Simal et al, 1998). It has also been demonstrated that ultrasonic waves improve the extraction level of calcium (Ca), potassium (K) and magnesium (Mg) from in vitro citrus culture (Arruda et al, 2003), the extraction level of polyphenols from tobacco (Gu et al, 2005) and the extraction level of polyphenols from strawberries (Herrera and Luque de Castro, 2005). Wang and Weller (2006) cited several studies that provide evidences about benefits and potential applications of ultrasound-assisted extraction of bioactive compounds from plants.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of the microwave approach is speed [13,14], but a disadvantage is inhomogeneous heating. The possible benefits of ultrasonic extraction are mass transfer intensification, cell disruption, and improved penetration effects [15]. Consequently, the combination of ultrasound and microwave radiation is a complementary technique that may exhibit the advantages of both methods.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies applying ultrasound bath in the sample treatment of soils and sediments [28][29][30][31], biological [32][33][34], nutritious [35,36]. However, in the case of forage samples, no study has yet been reported in the literature describing this technique for the extraction and quantification of phenolic acids.…”
Section: Introductionmentioning
confidence: 99%